THERMAL PERFORMANCE EVALUATION AND ANALYSIS OF THE EFFICIENT and SUSTAINABILITY SHELL AND TUBE HEAT EXCHANGER SYSTEM - Raghulkumar CHANDRASEKARAN; Xuejun QIAN; Seong LEE (Journal of Construction Project Management and Innovation)
Shell and tube heat exchanger (STHE) is one of the most attractive heat exchanger types and widely used in many industrial processes, power generation, and chemical process industries because of the STHE suits the high-pressure applications and harsh environment. STHE porotype consists of a shell with a bundle of tubes and several baffles inside it. The objective of the study is to model and analysis of thermal performance and heat transfer in the advanced STHE system by using ANSYS Fluent along with the experiment. The advanced computational simulation tool, ANSYS Fluent, and AutoCAD were used to model the STHE system along with the one shell (8” diameter), five tubes (1” diameter) and four baffles. In this study, steel was selected for shell materials, copper and brass was compared to select better performance materials for tubes. The constructed STHE model has meshed and analyzed under two mediums (water and biogas) with different thermal conditions. Besides, the experiment results from the STHE prototype were used to investigate conversion efficiency and analyze heat transfer. The analysis of variance (ANOVA) method was used to analyze the significant effect of hot water flow rate and inlet temperature on heat transfer of the STHE prototype. Results from simulation and Karen’s method indicated the heat release of the brass is lower than the copper in the system. Under various operating conditions, experimental results showed the conversion efficiency of the lab-scale STHE is a high range of 0.80-0.86. In addition, ANOVA results indicated that the hot water inlet temperature has a significant effect on heat transfer of STHE prototype.